Criminal Responsibility for Santet Practices in Simeulue Regency from the Perspective of Islamic Criminal Law - Umar, Mukhsin Nyak; Mustaqilla, Safira; Yahya, Faisal; Syahrima, Ima; Firdausia, Salsabila (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
Witchcraft or black magic is still believed to be an act that can cause harm to a person through occult science. The losses caused by witchcraft can be seen directly and clearly in witchcraft victims, but it is difficult to explain medically and scientifically. Although it cannot be proven based on criminal law, the impact of witchcraft can be known based on indications that are widespread in the victim, such as foreign objects found in the victim, causing physical and non-physical suffering for a long time, even causing the victim to die. The focus of this research is on how to resolve witchcraft cases through customary law in the Simeulue community. The method used is qualitative, with data obtained from interviews and supported by literature sources. The results of the study showed that the phenomenon of witchcraft in Langi Village, Teupah Village, and Suka Jaya Village in Simeulue Regency had a motive of displeasure between the perpetrator and the victim. Santet is not always used for evil, but can also be used for good, such as medicine, predicting the whereabouts of a person or lost item (tendung). In general, the people of Simeulue do not accept the presence of witchcraft (for evil) in their lives, but specific individuals still abuse witchcraft as a power to harm people. The abuse of witchcraft that causes others to suffer is not in line with the principles of Islamic criminal law. Witchcraft can be held accountable if proven to have committed a crime that causes harm to others, both physically, psychologically, or socially.